L’Unione europea come architetto della governance digitale globale: diritti fondamentali e regolazione delle piattaforme - Marsili, M. (Rassegna Europea, 2025)
This article critically analyzes the European Union’s role as a primary architect of global digital governance through its landmark regulatory framework—the General Data Protection Regulation (GDPR), the Digital Services Act (DSA), the Digital Markets Act (DMA), and the Artificial Intelligence Act (AI Act). It positions the EU’s strategy at the intersection of digital human rights protection, the pursuit of technological sovereignty, and intensifying geopolitical competition. The study examines inherent tensions between strict regulation and innovation, global normative ambition and critical technological dependencies, and high ethical principles versus implementation complexity. It argues that the EU’s success hinges on building a virtuous ecosystem combining rigorous enforcement, strategic investments, value-based international cooperation, and sustained academic and civil oversight. Ultimately, the EU’s endeavor represents an unprecedented experiment to offer a human-centric alternative to digital development—one that prioritizes democracy, fundamental rights, and justice over unchecked commercial or authoritarian logics.